2005
DOI: 10.1140/epja/i2004-10087-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-neutrino double- β decay of 94 ⩽ A ⩽ 110 nuclei for the 0+ → 0+ transition

Abstract: The two neutrino double beta decay of 94,96 Zr, 98,100 Mo, 104 Ru and 110 Pd nuclei for 0 + → 0 + transition is studied in the PHFB model in conjunction with the summation method. In the first step, the reliability of the intrinsic wave functions has been established by obtaining an overall agreement between a number of theoretically calculated spectroscopic properties and the available experimental data for 94,96 Zr, 94,96,98,100 Mo, 98,100,104 Ru, 104,110 Pd and 110 Cd isotopes. Subsequently, the PHFB wave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
80
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 70 publications
12
80
0
Order By: Relevance
“…In the present work, we use the same wave functions as used in the earlier works [50,51,74,75]. It has been already shown that [50], the experimental excitation energies of 2…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, we use the same wave functions as used in the earlier works [50,51,74,75]. It has been already shown that [50], the experimental excitation energies of 2…”
Section: Resultsmentioning
confidence: 99%
“…The maximum change in E 4 + and E 6 + energies with respect to PQQ 1 interaction [74,75] Table I, the Fermi, Gamow-Teller and tensor components of NTMEs M (0ν) for 100 Mo are presented without (HOC -3rd column) and with the SRC (HOC+SRC -4th to 6th columns) to exhibit the role of HOC as well as the SRC explicitly. To test the validity of closure approximation used in the present work, the NTMEs M (0ν) are also calculated for A/2 in the energy denominator in the case of HOC+SRC given in 7th to 9th columns of Table I.…”
Section: Resultsmentioning
confidence: 99%
“…One can compare this (4) value with the calculated value, M 2ν = 0.058 [24]. The obtained precise value for M 2ν will be used to fix g pp parameter and improve the M 0ν calculations for 96 Zr.…”
Section: ν Nmementioning
confidence: 77%
“…Two values for the parameter g A are generally agreed upon and the NME is computed using both g A = 1.0 and g A = 1.25. Recently a new approach (Projected Hartree-Fock-Bogoliubov -PHFB model) was developed [24,20,25] which can predict the M 2ν and M 0ν values.…”
Section: ν Nmementioning
confidence: 99%
“…It means that the suppression of M 0ν can be associated with the large deformation of initial and final nuclei and large value of A. Before the effect of deformation on M 0ν for nuclei with smaller A was associated with difference in deformations of the initial and final nuclei [43,46,47]. (4) - (7) imply that the half-lives are determined by the following properties of the initial and final atoms:…”
Section: νmentioning
confidence: 99%